Theoretical Calculation and Experimental Verification of Wind-Driven Rain Aerodynamic Forces on the Bridge Main Beam - Xu Lei; Lian Shen; Zhengqing Chen; Xuewen Zhang; Chenglong Wei; Yan Han (Atmosphere, 2023)
Regarding the issue of changes in the aerodynamic force of the bridge main beam under the action of wind-driven rain, this article explores the changes in air density caused by rainfall, the calculation theory of raindrop impact force and its simplified mass-weighted equivalent method (MWEM), and the calculation method of water accumulation thickness on the surface of the main beam. The calculation shows that the changes in air density caused by rainfall can be ignored, and the error of the MWEM increases with the increase in rainfall intensity; however, even at a rainfall intensity of 709 mm/h, the deviations in the MWEM value of the horizontal and vertical raindrop impact force is only about +5% and −4%, respectively. Then, based on the above analysis, a calculation model for the aerodynamic three-component forces of the main beam caused by rainfall under the action of wind-driven rain is provided. Finally, taking two typical main beam sections as an example, static three-component force tests are carried out on the main beam model under different rainfall intensities. The experimental results show that the drag coefficient variations obtained through the MWEM are in good agreement with experimental data, which proves the correctness of the theoretical model of the raindrop impact force. But for the lift and torque coefficient, the differences between theoretical and experimental values are much more significant than the drag coefficient, and it increases with the increase in rain intensity. It can be seen that the surface ponding model and influence of rainfall intensity need to be further explored. In summary, the theoretical calculation method for the additional aerodynamic force of wind-driven rain on the main beam proposed in this article is convenient and practical, and it can provide a certain reference for the rapid safety assessment of bridges under extreme meteorological conditions.